1999
DOI: 10.1007/s004390050923
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of gene conversion in the evolution of the human ?-like globin gene family

Abstract: Gene conversion is referred to as one of two types of mechanisms known to act on gene families, mainly to maintain their sequence homogeneity or, in certain cases, to produce sequence diversity. The concept of gene conversion was established 20 years ago by researchers working with fungi. A few years later, gene conversion was also observed in the human genome, i.e. the gamma-globin locus. The aim of this article is to emphasize the role of genetic recombination, particularly of gene conversion, in the evoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 81 publications
2
25
0
1
Order By: Relevance
“…This particular event suggests non-reciprocal transfer of DNA sequences from one chromosome to another by which a mutant allele induces a normal allele to convert into a mutant allele (Shiokawa et al 1989;Starck et al 1990). The existence of a mutation on different β-globin frameworks can be explained by an event of interallelic gene conversion also (Fukumaki and Fucharoen 1991;Papadakis and Patrinos 1999). In a study among the Thai population (Ohashi et al 2004) four major haplotypes (H1-H4) were found and H1 haplotype was appeared to have arisen from the H2 haplotype by a single mutation.…”
Section: Origin and Spread Of Hemoglobin Ementioning
confidence: 99%
“…This particular event suggests non-reciprocal transfer of DNA sequences from one chromosome to another by which a mutant allele induces a normal allele to convert into a mutant allele (Shiokawa et al 1989;Starck et al 1990). The existence of a mutation on different β-globin frameworks can be explained by an event of interallelic gene conversion also (Fukumaki and Fucharoen 1991;Papadakis and Patrinos 1999). In a study among the Thai population (Ohashi et al 2004) four major haplotypes (H1-H4) were found and H1 haplotype was appeared to have arisen from the H2 haplotype by a single mutation.…”
Section: Origin and Spread Of Hemoglobin Ementioning
confidence: 99%
“…Data on interparalog conversion come mainly from the occasional detection of variant or pathologically mutated genes in which an altered sequence tract can be shown to have originated in a paralogous gene copy (Collier et al 1993;Papadakis and Patrinos 1999;Ogasawara et al 2001). Rates for such processes cannot be easily deduced, but tract lengths are typically estimated as a few hundred base pairs.…”
Section: Genome Research 841mentioning
confidence: 99%
“…Fredman et al (2004) defined a new type of polymorphismmultisite variation (MSV)-representing the sum of the signals from many individual duplicon copies that vary in sequence content because of duplication, deletion, or gene conversion, and attributed 28% of the SNPs in duplicons to MSVs. Meiotic gene conversion, favored by high sequence homology between tandem-arrayed or inverted DNA segments, leads to concerted evolution of duplicons (Hurles 2001;Bettencourt and Feder 2002) and the spread of mutations (Tusié-Luna and White 1995;Papadakis and Patrinos 1999;Boocock et al 2003). Highly similar DNA segments also favor nonallelic homologous crossing-over coupled with rearrangements, leading to genomic disorders (Stankiewicz and Lupski 2002;Shaw and Lupski 2004).…”
mentioning
confidence: 99%